2010
DOI: 10.2298/hemind100614045z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon dioxide content in the biogas to nitrogen oxides emissions

Abstract: Fuels derived from biomass are an alternative solution for the fossil fuel shortage. Usually this kind of fuels is called low calorific value fuels, due to the large proportion of inert components in their composition. The most common is carbon dioxide, and its proportion in biogas can be different, from 10 up to 40%, or even more. The presence of inert component in the composition of biogas causes the problems that are related with flame blow off limits. One of the possibilities for efficient combustion of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The authors of [23] showed that CO occurs due to low combustion temperature, while the low level of NO x is caused by a small percentage of nitrogen in straw and optimal combustion temperature. Furthermore, the authors of [24] showed that, with the increase in CO 2 , the emission of NO x is reduced and the authors of [22] showed that the concentration of NO can be reduced with a higher concentration of SO 2 . In addition, the low levels of NO x can be achieved by coupling the DeNO x catalyst with urea to construct an in-situ NH3-SCR system during the combustion process, as discussed in [25].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [23] showed that CO occurs due to low combustion temperature, while the low level of NO x is caused by a small percentage of nitrogen in straw and optimal combustion temperature. Furthermore, the authors of [24] showed that, with the increase in CO 2 , the emission of NO x is reduced and the authors of [22] showed that the concentration of NO can be reduced with a higher concentration of SO 2 . In addition, the low levels of NO x can be achieved by coupling the DeNO x catalyst with urea to construct an in-situ NH3-SCR system during the combustion process, as discussed in [25].…”
Section: Introductionmentioning
confidence: 99%